Certification of homestay operation in Malaysia: a critical analysis on the procedures and guidelines in registration of homestay's Malaysia / Nurhusna Sidek, Fairuz Fazeera Nordin, Nur Fardhiah Mohd Nawawi - Sidek, Nurhusna; Nordin, Fairuz Fazeera; Mohd Nawawi, Nur Fardhiah (2011)
The homestay programme was officially established in Malaysia since 1995 and die number of operators participating in the homestay programme increases from year to year. However, the number of illegal homestays, i.e. number of homestay operators tiiat are not registered witii die Ministry of Tourism (MOTOUR) also increased from time to time. This research explores the guidelines of homestay registration process and certification that is provided by MOTOUR in comparison with the Taiwan law. The objective of tliis research is to critically analyse the regulation of homestay in Malaysia and to identify the weakness of the existing laws and policies in die registration of homestay programme in Malaysia. In providing suggestion to the betterment of the laws and policies of the homestay programme in Malaysia, the comparative study with the law and policies in Taiwan is made. Hence, the research hopes to be a source of reference to the related agencies on registration of the homestay programme.